The Relationship between Mother's Knowledge and Attitudes and Giving Early Complementary Breastfeeding at UPTD Boronadu Health Center South Nias Regency in 2022 - Fau, Yentiria; Painem, Painem; Purba, Edy Marjuang; Sari, Febriana; Situmorang, Tetti Seriati; Nainggolan, Anna Waris; Sinaga, Rosmani (Sean Institute, 2022)
Giving complementary breastfeeding too early is one of the inhibiting factors for exclusive breastfeeding. The results of a preliminary survey conducted at the UPTD Health center Boronadu South Nias Regency where interviews were conducted with mothers and it was found that 8 mothers did not know that babies should only be given breast milk until they were 6 months old and they agreed that babies less than 6 months old were given additional food other than breast milk such as bananas, tea, formula milk and other foods. This study aims to determine the relationship between knowledge and attitudes of mothers regarding early complementary breastfeeding at the UPTD Health center Boronadu South Nias Regency in 2022. This study was an analytic observational study with a cross sectional design. The population is all mothers having babies more than 6 months at the UPTD Health center Boronadu South Nias Regency, namely 118. The number of samples based on the sample formula is 48 people. There is a significant relationship between the knowledge (p=0.022) and attitudes (p=0.006) of postpartum mothers and the provision of early complementary breastfeeding in the UPTD Work Area of the Boronadu Health Center in 2022. It is also hoped that health workers at the UPTD Boronadu Health Center will be able to further increase public knowledge regarding complementary breastfeeding and increasing its role in efforts to achieve exclusive breastfeeding through counseling, which can be carried out at village meetings, posyandu and counseling during pregnancy checks.